The management strategies of Qur'an memorization in enhancing the competitiveness of students at Rumah Tahfizh Al-Furqon, Riau - Anas, Anas; Muslih, Muslih; Firdaus, Abdullah (Asatiza: Jurnal Pendidikan, 2024)
The management of the Qur'an memorization program at Rumah Tahfizh Al-Furqon, Mugomulyo, Sungai Batang Subdistrict, Indragiri Hilir Regency, Riau, plays a crucial role in enhancing the competitive advantage of its students. This study aims to analyze the management strategies implemented and their impact on the quality of memorization and character development of the students. Using field research with a phenomenological approach, this study involved Qur'an memorization teachers and students as respondents. Data collection techniques included interviews, observation, and documentation. The findings reveal that the program not only improves the students' memorization skills but also plays a key role in fostering discipline, responsibility, and leadership among them. Rumah Tahfizh Al-Furqon significantly contributes to shaping a generation that is both competitive and of high moral character within society, while also strengthening the institution's role in Islamic education. This research can serve as a reference for other Qur'an memorization institutions in developing similar programs.